1996
DOI: 10.1016/0014-5793(95)01513-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the heparin‐binding domain of boar spermadhesins

Abstract: Boar spermadhesins are a group of seminal plasma, heparin-binding proteins which appear to be involved in sperm capacitation and gamete interaction. Using a proteolytic protection assay we have identified regions of AQN-I, AQN-3, PSP-I and AWN which remain attached to a heparin-Sepharose column following in-column digestion of bound spermadhesins with chymotrypsin and elastase. In addition, the complete amino acid sequence of spermadhesin AWN was synthesized as overlapping peptides, and their ability to bind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…The findings of our previous study demonstrated the presence of high molecular weight zinc-binding protein ligands in boar and canine seminal plasma (18,19). Under the influence of denaturing and reducing agents, they dissociate to low molecular weight polypeptides that together with sperm-adhesive properties are also present in large quantities in boar, bull, and stallion seminal plasma (8,9,31). The spermadhesins' structure and function are well-documented, in contrast to canine seminal plasma proteins with almost unknown properties.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our previous study demonstrated the presence of high molecular weight zinc-binding protein ligands in boar and canine seminal plasma (18,19). Under the influence of denaturing and reducing agents, they dissociate to low molecular weight polypeptides that together with sperm-adhesive properties are also present in large quantities in boar, bull, and stallion seminal plasma (8,9,31). The spermadhesins' structure and function are well-documented, in contrast to canine seminal plasma proteins with almost unknown properties.…”
Section: Discussionmentioning
confidence: 99%
“…These spermadhesins are thought to stabilize the plasma membrane over the acrosomal vesicle and are mainly released from the spermatozoal surface during capacitation (Sanz et al, 1993;Dostàlovà et al, 1994;Calvete et al, 1997). A phosphorylethanolamine-binding region has been mapped to a discontinuous region of AWN comprising residues 6-12 and 104-108 (Ensslin et al, 1995), and a conformational heparin-binding surface, which partly overlaps with the phosphorylethanolaminebinding region, resides in an opposite location to the carbohydrate-binding region of the spermadhesin (Calvete et al, 1996a).…”
Section: Sperm-oviduct Interactionmentioning
confidence: 99%
“…the N-terminal domain of TSG-6, and not with the full-length protein (19 -23). However, the CUB domain, known as a GAG-binding domain from studies with other proteins, may also affect the binding of TSG-6 to GAGs (17,24,25). Therefore, the binding of full-length, glycosylated TSG-6 protein to GAGs deserves additional study.…”
Section: Tnfmentioning
confidence: 99%